The management of exercise-induced anaphylaxis in a Chinese child with biologics: a case report - Jiang, Nannan; Xiang, Li; Huang, Huijie; Zhang, Xudong (Frontiers in Allergy, 2024)
Exercise-induced anaphylaxis (EIA) is a rare and potentially life-threatening disorder. In difficult to control and refractory cases of EIA, biologics such as omalizumab and dupilumab have shown promise, with documented successful outcomes. Here, we present a case of EIA with lipid transfer protein (LTP) sensitization successfully treated with omalizumab with long-term follow-up. A 12-year-old girl presented to our allergy department because of recurrent episodes of EIA, with no specific food ingestion before exercise. Allergen testing revealed sensitization to weed pollens, particularly mugwort (76.1 kUA/L) and Alternaria alternata (10.8 kUA/L). Allergen component testing indicated sensitization to LTP components from mugwort Art v 3 (49.9 kUA/L), wheat Tri a 14 (2.03 kUA/L), and peach Pru p 3 (11.5 kUA/L), with a negative result for omega-5 gliadin. Despite initial prophylactic treatment with budesonide–formoterol (80/4.5 μg) and cetirizine (10 mg) before exercise, the patient still experienced EIA; she was then recommended for dupilumab therapy (an initial dose of 600 mg, followed by 300 mg every 2 weeks for six doses). However, even while undergoing dupilumab therapy, she suffered two anaphylactic episodes after running 800–1,000 m. With the patient's consent, a trial of omalizumab was initiated (injections of 300 mg every 4 weeks). After 2 months of omalizumab therapy, the patient showed significant improvement. She had been engaging in physical exercise three times a week and experienced a mild episode of urticaria. There were no further episodes of anaphylaxis or emergency room visits. By the fourth month of omalizumab treatment, she was able to consume food normally even just before exercising and had returned to her full activity level without any restrictions. This case presents the first successful off-label use of omalizumab in the prevention of EIA in the Chinese population. It is concluded that omalizumab may be helpful in resolving EIA symptoms, as evidenced by this case of successful long-term use.